Economics on trial: the use and abuse of economic methods in third party tobacco litigation. (27th November 2006) - Max, Wendy; Tsoukalas, Theo
Abstract : Objective: To analyse how the tobacco industry responded to economic models and methods used in third party payer tobacco litigation that has occurred since 1994. Methods: Identified 12 third party payer cases and reviewed the transcripts using WinMax qualitative software. Focused on defendant's opening and closing statements, followed by trial testimony, depositions, and plaintiff's transcripts. Results: Tobacco industry defendants tried to create doubt and confusion about whether or not smoking caused disease and by extension led to health care costs; argued that the economic models used were not legitimate and were not appropriate for estimating the costs incurred by plaintiffs; and criticised the data sources used because they did not consist of the individuals whose health care costs were being sought. Conclusions: Faced with a new and unprecedented wave of anti-tobacco litigation from third party payers, the tobacco industry tried to adapt strategies that had been used successfully in the past—creation of unfounded doubt and confusion, and manipulation of the discovery process to force plaintiffs to withdraw or concede defeat. The strategies failed because credible economic models of the health care costs of smoking had been developed that were able to quantify the damages to a large group of health care recipients, because plaintiff's attorneys were able to commit significant resources and willing to undertake substantial financial risk to defend their new legal approaches, and because previous arguments related to individual responsibility were deemed irrelevant in third party litigation.